Exploring capability maturity models and relevant practices as solutions addressing information technology service offshoring project issues*. Issue 3 (3rd July 2018) - Salman, Rosine; Daim, Tugrul; Raffo, David; Dabic, Marina
Abstract: This research investigated Capability Maturity Models (CMMs) / Capability Maturity Model Integration (CMMI) best practices and their effects on managing and mitigating critical issues associated with offshore development. Using a web-based survey, data were collected from 451 Information Technology (IT) and software development firms in the US. The results of the analysis show that IT companies applying CMM/CMMI models have fewer issues associated with IT offshoring. When US IT companies utilizing and incorporating different practices from Team Software Process (TSP) and People CMM into CMMI-DEV/SVC is CMMI for Development and Services (CMMI-DEV/SVC) and CMMI for Acquisition (CMMI-ACQ), they have fewer offshoring issues related to language barriers and cultural differences.